EFFECTIVENESS OF AI-BASED ENGLISH LANGUAGE LEARNING APPS IN IMPROVING LISTENING SKILLS - Iin Almeina Loebis (Lingeduca: Journal of Language and Education Studies, 2025)
The increasing integration of Artificial Intelligence (AI) in educational technologies has revolutionized language learning, particularly in enhancing listening skills—an area often regarded as challenging for English as a Foreign Language (EFL) learners. Despite the growing popularity of AI-based English learning applications, empirical evidence on their effectiveness remains limited. This study aims to examine the effectiveness of AI-powered language learning apps in improving the listening skills of EFL learners. Employing a quasi-experimental design, the research involved 60 undergraduate students divided into an experimental group using AI-based applications and a control group receiving traditional instruction. Data were collected through pre-tests and post-tests, along with user experience questionnaires. The findings revealed a significant improvement in the listening comprehension scores of the experimental group compared to the control group. Moreover, students reported increased motivation and engagement when interacting with AI-enhanced features such as speech recognition, adaptive feedback, and real-time listening exercises. The study concludes that AI-based English learning apps are effective tools for developing listening skills, offering personalized and interactive learning experiences. These results provide valuable implications for educators, app developers, and policymakers in integrating AI technology into language education.